2000
DOI: 10.1007/s001250050004
|View full text |Cite
|
Sign up to set email alerts
|

Significant improvement of apolipoprotein B-containing lipoprotein metabolism by insulin treatment in patients with non-insulin-dependent diabetes mellitus

Abstract: Cardiovascular diseases are the most common complications observed in Type II (non-insulin-dependent) diabetes mellitus [1]. The multiple abnormalities in lipoprotein metabolism frequently associated with Type II diabetes play an important part in the premature development of atherosclerosis in Type II diabetic patients. They generally have an increased plasma concentration of very low density lipoprotein (VLDL) particles that has been linked both to an increased synthetic rate and a decreased catabolic rate D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 40 publications
2
17
1
Order By: Relevance
“…Since lipoproteins are metabolically active in the plasma compartment, we expressed the production rates adjusted to plasma volume instead of body weight, as previously reported. 10,11 Our results indicate that insulin resistance significantly influences HDL metabolism since the insulin resistance index (HOMA) was negatively correlated with HDL cholesterol levels. Furthermore, apoA-I fractional catabolic rate was positively correlated with clinical (waist -hip ratio, waist circumference) and biological markers of insulin resistance (plasma fasting and post-load insulin levels, HOMA).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Since lipoproteins are metabolically active in the plasma compartment, we expressed the production rates adjusted to plasma volume instead of body weight, as previously reported. 10,11 Our results indicate that insulin resistance significantly influences HDL metabolism since the insulin resistance index (HOMA) was negatively correlated with HDL cholesterol levels. Furthermore, apoA-I fractional catabolic rate was positively correlated with clinical (waist -hip ratio, waist circumference) and biological markers of insulin resistance (plasma fasting and post-load insulin levels, HOMA).…”
Section: Discussionmentioning
confidence: 71%
“…Thus, data were normalized to the plasma volume of each subject, as previously reported. 10,11 Analytical methods Apolipoprotein and lipid assays. Concentrations of apoA-I were determined by immunoturbidimetry 24 with anti-apoA-I antibodies purchased from Boeringer Mannheim.…”
Section: Modellingmentioning
confidence: 99%
“…The following day, kinetic study was performed in the fed state. Food intake, with a leucinepoor diet (1700 kcal/day, 55% carbohydrates, 39% fats, and 7% proteins), was fractionated in small portions that were provided every 2 h starting 6 h prior to the tracer infusion up to the end of the study to avoid important variations in apolipoprotein plasma concentration, as previously performed by our group (18,19) and others (20). The endogenous labeling of apoA-I was carried out by administration of L- [1][2][3][4][5][6][7][8][9][10][11][12][13] C] leucine (99 atom %, w/v; Eurisotop, Saint Aubin, France), dissolved in 0.9% (w/v) NaCl solution.…”
Section: Methodsmentioning
confidence: 99%
“…A slight increase of VLDL-apoB production likely contributes to the hyperlipidemia in 1 patient (BIII3). It is most likely the consequence of her diabetes mellitus rather than of Apoa5 truncation because her VLDL-apoB PR is as usually observed in type 2 diabetic patients (22,23). Accordingly, recent experimental studies indicated that Apoa5 does not modulate hepatic VLDL production (24) but induces an LPL-dependent acceleration of the catabolism of TG-rich lipoproteins (24)(25)(26).The increase in IDL pool despite the reduced VLDL catabolism is likely due to the 22-fold increase in VLDL pool leading to a residual conversion into LDL.…”
Section: Figurementioning
confidence: 99%